Social media and disinformation for candidates: the evidence in the 2024 Indonesian presidential election - Subekti, Dimas; Yusuf, M.; Saadah, Maratun; Wahid, Makmun (Frontiers in Political Science, 2025)
This study aims to examine how the pattern of disinformation spread on social media to candidates in the 2024 Indonesian presidential election. This research uses a qualitative method with a case study approach. The findings of this study explain that in the 2024 elections in Indonesia, social media had a significant role in spreading disinformation. Each candidate becomes a victim of disinformation attacks on social media by attacking from the side of character assassination and political issues. Then, the pattern of disinformation in the 2024 elections was more dominant on social media channels that supported the emergence of video and text characters, such as Facebook, YouTube, and Tiktok. Furthermore, the spread of disinformation to candidates harms their participation in the 2024 elections. This research implies that digital technology intervention significantly influences candidates in election contestation. Moreover, social media has become a sophisticated facility for spreading disinformation by political actor teams to utilize as a form of electoral attack effort.